ANALYSIS OF FACTORS RELATED TO THE SELF-EFFICACY OF INDONESIAN RED CROSS (IRC) MEMBER STUDENTS IN CARRYING OUT AHA 2020 STANDARD CARDIOPULMONARY RESUSCITATION IN DENPASAR CITY - Yusniawati, Yustina Ni Putu; Sanjaya, I Wayan Edi; Putra, I Gde Agus Shuarsedana; Lewar, Emanuel Ileatan; Putri, I Gusti Ayu Nandita Arta (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Abstract Background: Cardiac arrest is a condition of the heart that loses its function suddenly to pump blood throughout the body. Cardiac Arrest has events that take place very quickly and cannot be predicted so that it becomes an important concern in the world of health. Cardiopulmonary Resusitatiom (CPR) training programs for IRC students are increasingly emphasized to increase bystander CPR which is very low, while some cause low interest of students in doing CPR, especially mouth to mouth because they are afraid to do CPR because they feel wrong if they do CPR incorrectly, physically cannot do CPR, fear of harming the individuals helped, fear of contracting diseases contagious, the belief that the person has died. Objective: Analyze the factors of self- physicalizing (knowledge, attitude, motivation and awareness) of IRC students in providing cardiopulmonary resuscitation (CPR) in cardiac arrest patients Method: This research is a type of quantitative research with a cross sectional approach with purposive sampling. Data collection was carried out for 2 months once using a direct questionnaire. The number of samples in this study was 300 respondents of IRC member students in Denpasar City. The inclusion criteria in this study are IRC member students from universities who are active in lectures, active as members of IRC Denpasar City, attending basic training IRC members are young and willing to be respondents. Process research directly and also written on the consent sheet becomes a research respondent and is given informed consent. After getting approval, participants can do the entire questionnaire for 30 minutes. The analysis test carried out is univariate analysis, which describes the characteristics of research respondents, analysis using sperm, multivariate analysis using logistic regression tests. Results: The results of the study obtained that knowledge P value = 0.022, attitude p value 0.026, motivation p value 0.017 and awareness p value 0.050. Awareness is the most influential variable with student preparedness (OR= 1,192), which means that poor awareness will cause low efficacy of undergraduate nursing students in helping patients with cardiac arrest by 1 time compared to the efficacy of IRC member students who have good awareness after the variables of knowledge, attitude, and motivation are controlled. Conclusion: There is a significant relationship between knowledge, attitudes, motivation and awareness with the efficacy of PMI member students in conducting CPR AHA 2020 where awareness is the most influential variable on the efficacy of IRC member students in conducting CPR AHA 2020.